Optimization of Kelulut Honey Addition on Organoleptic Quality of Pasteurized Goat Milk - Nurmasytha, Andi; Wibowo, Ari; Sulistyowati, Anastasya Dian; Divayanti, Fauziyyah; Wahyuningtyas, Amalina Nur; Adiputra, Kirana Dara Dinanti (Fakultas Peternakan Universitas Jambi, 2025)
Background: Increased public awareness of the importance of healthy living is one of the things that encourage increased consumption of goat milk because it contains antioxidants, more fatty acids, proteins, and minerals when compared to cow's milk and is easily digested for those who are intolerant to lactose, has a perishable nature so it needs to go through a heating process with pasteurization before consumption. Objective: This study aims to measure the optimization of kelulut honey addition on the organoleptic quality of pasteurized goat milk. Methods: Goat milk was heated, and when it reached 75°C, the product was constantly stirred and pasteurized for 15 seconds. Then, kelulut honey was added according to the treatment. The research parameters in sensory testing used 36 semi-trained panelists. Panelists assessed the characteristics of pasteurized goat milk drink products by adding different levels of honey using the scale method (rating scale 1-5). This study used a completely randomized design with five treatments (addition of 0%, 5%, 10%, 15%, and 20% honey levels) with three replications. If the results obtained show a significant difference, the Duncan test is continued. Results: The values of color, honey aroma, milk aroma, product viscosity, taste, and panelists' liking had a significant effect (P<0.01) on pasteurized goat milk with the addition of different levels of honey. Conclusion: The addition of honey improved the quality of organoleptic values of color, honey aroma, and viscosity of the product. The aroma of milk, flavor, and liking decreased as the addition of honey level increased. Based on the overall organoleptic assessment of panelists, pasteurized goat milk with the addition of 5%-10% honey level is a product that is accepted by the public.